Menggali Prinsip Kepemimpinan Pendidikan Rasulullah Dalam Membangun Pendidikan Yang Berkarakter Dan Berdaya Saing - Muhammad Yusron; Muhk Nursikin; Umi Wardatul Maghfiroh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Leadership in education plays a crucial role in creating an environment that supports the development of both character and academic quality in students. One relevant leadership model is that of Prophet Muhammad SAW, who emphasized moral values, closeness to the community, consultation, and setting a good example. In this era of globalization, education that is both character-driven and competitive requires leaders who focus not only on academic aspects but also on integrating noble values to shape superior individuals. Therefore, it is essential to explore the principles of Prophet Muhammad SAW’s leadership as a solution to the challenges in today’s education. This study aims to analyze the principles of Prophet Muhammad SAW’s leadership that can be applied in building character-based education that is also competitive. Additionally, this research provides recommendations for educational leaders, especially school principals, on how to implement these leadership values. The study employs a qualitative approach with a literature review methodology, gathering data from hadith, tafsir, and literature related to the leadership of Prophet Muhammad SAW, as well as educational leadership theories. The findings are expected to provide new insights into the development of value-based educational leadership, creating a competitive education system on a global scale.